PEMBENTUKAN KARAKTER ISLAMI SISWA MTS DARUL HIKMAH PRASUNG - M. As'ad Nahdly; Ahmad Amiq Fahman (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstract: Now days Indonesian people have faced many imbalances caused by source of education, especially for adolescent. There are many bad cultures influence them, example is they do impolite thing to teacher and parent. Education and programs for founding behaviour and characteristic is really needed. Basically, Islamic Education is education that proposed by Islamic teaching as an effort to fortify increasing of moral crisis day per day. Because of development of epoch, make students of Junior High School Darul Hikmah Prasung possible to avoid discipline such as absent from school without permit, do impolite to teacher, and all bad deeds. Here, Islamic education has very important rule to create behaviour (akhlaq) for each student so that they become adult, independent, and has kind behaviour. This research uses qualitative descriptive approach, and also use qualitative descriptive as technique of analyse. In process of collecting data, the writer uses methods of observation, interview, and documentation. Base on result of research, writer found that application of Islamic Education as an effort to create Islamic characteristic of student in Junior High School 13 Malang is running well. It can be proved by many activities that apply in school, such as Dhuha praying together (jamaah) before enter class of Islamic education, Dhuhur praying together (jamaah), pray and reading asmaul husna before lesson is began. These activities have done the rounds every day. And then, there is motivations to do good deed by good stories while learning process. From all the activities, students of Junior High School Darul Hikmah Prasung, they have showed positive behaviour upKeyword: Islamic Education, Islamic Character